Gender equity and social capital in smallholder farmer groups in central Mozambique - Gotschi, Elisabeth; Njuki, Jemimah; Delve, Robert J. (Informa UK Limited, 2008)
This case study from Bu´zi district, Mozambique investigated whether gender equality, in terms of male and female participation in groups, leads to gender equity in sharing of benefits from the social capital created through the group. Exploring the complex connection between gender, groups, and social capital, we found that gender equity is not necessarily achieved by guaranteeing men and women equal rights through established by-laws, or dealing with groups as a collective entity. While there were no significant differences in the investment patterns of men and women in terms of participation in group activities and contribution of communal work, access to leadership positions and benefits from social capital were unequally distributed. Compared with men, women further found it difficult to transform social relations into improved access to information, access to markets, or help in case of need.